The effects of substituting B for Cu on the magnetic and shape memory properties of CuAlMnB alloys - Aydogdu, Y.; Turabi, A. S.; Aydogdu, A.; Vance, E. D.; Kok, M.; Kirat, G.; Karaca, H. E. (Springer Heidelberg, 2016)
The effects of B addition on the magnetization, mechanical and shape memory properties in Cu70-xAl24-Mn6Bx at.% (x = 0, 1, 2, 3, 4) alloys have been investigated. The ductility was decreased, while the strength was improved with B addition. Transformation temperatures were increased with B content due to increased e/a ratio. Martensite start temperature of B-free CuAlMn was found to be 37.3 degrees C and increased to 218.8 degrees C with 4 % B addition. B-free CuAlMn exhibited shape memory effect with a recoverable strain of 2.25 % under 200 MPa and a perfect superelasticity with a recoverable strain of 2.5 % at 163 degrees C. B addition degraded the shape memory properties and eventually resulted in the lack of recoverable strain. In addition, saturation magnetization was increased with B content. Moreover, the addition of B slightly decreased the ductility of the alloy. It was found that the magnetization, mechanical and shape memory properties CuAlMn alloys can be tailored by quaternary alloying with B.
Keywords: Mechanical-Properties; Transformation Temperatures; Phase-Transformation; Boron Addition; Microstructure; Stability